The impact of using mobile learning on academic achievement and the development of expressive reading skills in the English language course for secondary school students in the city of Jeddah - Albaeth, Abdullah Yahya (Journal of Educational and Psychological Sciences, 2024)
The current study aimed to identify the effect of using mobile learning on academic the aim of the current research is to identify the impact of using mobile learning on academic achievement and the development of expressive reading skills in the English language course for secondary school students in the city of Jeddah. The researcher used the experimental approach with a quasi-experimental design, based on two experimental groups (experimental, control) among a sample of students. The secondary stage in the city of Jeddah, numbering (60) students, was divided equally into the two groups. The appropriate statistical treatments were determined, and the results were reached. 1- There are statistically significant differences at the level (α≤0.05) between the post-average scores of the experimental group and the scores of the control group in favor of the experimental group in reading skill, listening skill, and speaking skill, and There are statistically significant differences at the level (α≤0.05) between the post-average scores of the experimental group and the scores of the control group in academic achievement (total test results) in favor of the experimental group, The researcher recommends: 1-Activating the use of mobile learning and benefiting from its applications, and urging students to benefit from it in developing English language skills, 2-It is necessary to hold a scientific symposium for members of the English language teaching staff to know their opinions and attitudes towards the benefit and feasibility of employing such advanced techniques in developing English language skills.
Keywords: mobile learning; academic achievement; expressive reading skills